Anisotropy of intact loess under dynamic and static loads: insights from macroscopic and microscopic tests - Wen, Shaojie; Li, Dongfeng; Yin, Zhiyong; Zhang, Wuyu (Frontiers in Earth Science, 2025)
To deeply investigate the anisotropic mechanical properties of intact loess under static and dynamic loads, static and dynamic triaxial tests were conducted on samples with different deposition directions (0°, 30°, 45°, 60°, 90°). Combining macroscopic mechanical tests with microstructural analysis, the anisotropic response mechanisms were systematically revealed. The study results indicate that under both static and dynamic loads, the stress-strain relationship curves of intact loess at different sampling angles exhibit significant anisotropy. Both the deviatoric stress at failure and the initial dynamic elastic modulus display anisotropy. The nonlinear pattern with varying angles is as follows: the maximum value occurs at 0°, followed by sequential decreases at 30°, 60° (slightly lower than 30° in some cases), and 45°, with the minimum value appearing at 90°. The consolidation effect of confining pressure weakens the original structural strength of loess, leading to a decrease in the initial dynamic elastic modulus as confining pressure increases, but the anisotropic characteristics remain pronounced. After the tests, the pore structure of loess changed from a large-pore, weakly cemented open structure to a fine and dense interlocking structure. The particle morphology transformed from single-grain and angular to flocculent and ellipsoidal. These microstructural evolutions constitute the intrinsic mechanism of the macroscopic mechanical responses. The findings of this study provide important experimental evidence and theoretical support for the design, construction, and disaster prevention of complex engineering projects in loess regions.